Soil carbon distribution in three land uses of Gambari Forest Reserve Area, Oyo State (2019)
Soil adsorptive property is considered for mitigation of climate change in the terrestrial ecosystem. However, there are inconsistent findings on the contribution of aggregate sizes to carbon sequestration in soil depths. Inappropriate land-use practices cause increasing greenhouse gases in the atmosphere. Detail estimation of carbon associated with soil aggregates in different land-uses is required to identify land-use practice that promotes carbon accumulation. Therefore, the objective of the study was to investigate distribution of organic carbon associated with the soil aggregate sizes in selected land-uses. Three (30 m x 30 m) sample plots were established randomly in each of Natural Forest (NF), Plantation Forest (PF) and Cultivated Land (CL). Soil core samples were collected at 0-15, 15-30 and 30-45 cm depths using steel soil corers). Soil core samples were oven-dried at 105°C and bulk densities were computed. Oven-dried soil sample of 100 g was separated into five aggregates (>2, 2-1, 1-0.5, 0.5-0.05 and <0.05 mm) using the dry sieve procedure. Each aggregate (10 g) was heated in Muffle furnace at 500oC for 4 hours for soil carbon estimation. Aggregate sizes >2mm dominated NF and PL while 0.05 mm dominated CL. There was no significant difference in the distribution of aggregate sizes of NF and CL, except PL. The three land-use practices have the same proportion of aggregate 1-0.5mm at topsoil. Macro- and micro-aggregates influence soil carbon content in natural forest and plantation forest, respectively. Depth and land-use change caused re-distribution of carbon on soil aggregate sizes.